Desenvolvimento de uma metodologia eletroanalítica para o monitoramento de traços de metais pesados em estruvita usada como fertilizante na agricultura orgânica - Vasconcellos, Maria de Lourdes Soprani (2019)
In recent years, organic agriculture has been increasing the productivity of natural fertilizers, ensuring food quality, as well as promoting sustainability. Among the natural fertilizers, there is a prominence for struvite (MgNH4PO4·6H2O), a compound that can be precipitated from the urine by the addition of magnesium oxide (MgO), and has a large amount of macronutrients. However, some toxic substances in the urine used to produce the fertilizer can contaminate the soil, food crops and even water resources. Among the toxic substances, the presence of heavy metals is the main concern, as these substances can diffuse to the aquatic environment, accumulate in soils producing an adverse effect on human health and the ecosystem. This work presents an electroanalytical methodology using the Square Wave Anodic Stripping Voltammetry (SWASV) technique associated with screen-printed gold electrodes (SPGEs) to provide the simultaneous determination of lead, copper and mercury in struvite. The proposed method had a low detection limit for the analytes of interest, where it was possible to detect 1.31 μg L-1 of Pb(II), 1.99 μg L-1 Cu(II), and 0.87 μg L- 1 for Hg(II) in the linear range between 10 and 50 μg L-1. To obtain such values, the following parameters were used: -0.4 mV and 90 s for the potential and time of deposition; 2 mV for step potential; 30 mV for amplitude and 10 Hz for frequency, in HCl 0.05 mol L-1. The technique employed permitted a quantification limit of 4.37 μg L 1for Pb(II), 6.62 μg L-1 for Cu(II), and 2.89 μg L-1. The analysis performed on the struvite sample enabled the determination of Pb(II), being possible to find the concentration of 1.70 ± 0.30 μg-1. For Cu(II) and Hg(II), they were below the LOD of the proposed methodology, however, they are below the limits established by the Brazilian regulatory agency. In addition, the use of SWASV associated with SPGEs presented high recovery values (90%, 92% and 111% for Pb (II), Cu (II) and Hg (II)), indicating that there was no matrix effect during the analysis of struvite. Couple up the qualities of being a direct analysis methodology, with quick answers, it allows fast and direct trace analysis, free from interference of the sample matrix, the present study made possible the quality control of struvite use as a fertilizer in organic agriculture.